Did COVID-19 Change Life Insurance Offerings? - Timothy F. Harris; Aaron Yelowitz; Charles Courtemanche (Institute of Labor Economics (IZA), 2020)
The profitability of life insurance offerings is contingent on accurate projections and pricing of mortality risk. The COVID-19 pandemic created significant uncertainty, with dire mortality predictions from early forecasts resulting in widespread government intervention and greater individual precaution that reduced the projected death toll. We analyze how life insurance companies changed pricing and offerings in response to COVID-19 using monthly data on term life insurance policies from Compulife. We estimate event-study models that exploit well-established variation in the COVID-19 mortality rate based on age and underlying health status. Despite the increase in mortality risk and significant uncertainty, we find limited evidence that life insurance companies increased premiums or decreased policy offerings due to COVID-19.
Keywords: D81; I13; 330; 2019 novel coronavirus; SARS-CoV-2; COVID-19; term life insurance; severe acute respiratory syndrome 2